On the relationship between the mechanical strength and mineral microstructure of biotite granite under temperature influence - Huang, Yuyang; Li, Tianbin (Frontiers in Earth Science, 2023)
Many studies are currently focusing on the mechanical properties of granite from macroscopic and microscopic perspectives, but only several studies on the influence of rock mineral composition on the mechanical properties using a combined macro-micro assessment. The biotite granite in the Gaoligong Mountains was selected as the research object, and the variation strength characteristics at 20 ~130 °C were obtained through uniaxial compression experiments. The rock's uniaxial compressive strength and elastic modulus reached peak values at 40 °C. The main mineral components of the rock determined by X-ray powder diffraction were quartz, biotite, albite, and potash feldspar. With Material Studio (MS) software, molecular dynamics simulations were carried out on the crystal models of quartz, biotite, albite, and potash feldspar at 20 ~130 °C, and relevant mechanical parameters were calculated. The macroscopic and microscopic experimental data were compared and analyzed. The results show that: (1) due to the thermal expansion of minerals in the rock, the original cracks between particles are partially closed, and the sample strength is the largest at 40 °C; (2) temperature mostly affects quartz and biotite phases, and the rock strength increases first and then decreases with the temperature increase. The mechanical properties of albite and potash feldspar are less affected by temperature; (3) macroscopic and microscopic experimental results show that the rock strength reaches the peak value in a certain temperature range. The obtained critical temperature is different because the rock sample also contains a small amount of argillaceous rock, siliceous rock, phyllite, and some siliceous and calcareous cement beside the main mineral composition; (4) The structural changes of quartz and biotite are affected by temperature. The bond length of the quartz crystal decreases while that of the biotite crystal first increases and then decreases with the temperature. The mechanism of the temperature influence on the increase of the rock strength is different for these two crystal phases, and it requires further exploration.